2013
DOI: 10.1152/jn.00764.2012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in spectral profiles between rostral and caudal premotor cortex when hand-eye actions are decoupled

Abstract: The aim of this research was to understand how the brain controls voluntary movement when not directly interacting with the object of interest. In the present study, we examined the role of premotor cortex in this behavior. The goal of this study was to characterize the oscillatory activity within the caudal and rostral subdivisions of dorsal premotor cortex (PMdc and PMdr) with a change from the most basic reaching movement to one that involves a simple dissociation between the actions of the eyes and hand. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 101 publications
4
14
0
Order By: Relevance
“…Further, recent anatomical studies have found altered white matter integrity in concussed adolescents, younger adults with concussion history, and older adults with concussion history that involved those pathways connecting frontal and parietal regions [ 34 37 ]. These data complement our group’s findings on the crucial role played by such fronto-parietal networks in integrating thought and action [ 10 , 14 , 19 , 20 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Further, recent anatomical studies have found altered white matter integrity in concussed adolescents, younger adults with concussion history, and older adults with concussion history that involved those pathways connecting frontal and parietal regions [ 34 37 ]. These data complement our group’s findings on the crucial role played by such fronto-parietal networks in integrating thought and action [ 10 , 14 , 19 , 20 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…While some research suggests that a strong relationship exists (Ray and Maunsell 2011; Zanos et al 2011, 2012), others suggest a difference between spiking and high gamma activity (Flint et al 2012; Pesaran et al 2002). To remain consistent with our laboratory's previous work, we decided to only include data from below 60 Hz (Sayegh et al 2013).…”
Section: Data Analysesmentioning
confidence: 97%
“…Two rhesus monkeys (female Macaca mulatta, both 5.2 kg) were trained to perform a visually instructed delayed reaching task under coupled and decoupled eye-hand conditions, as described previously (Hawkins et al 2013;Sayegh et al 2013). All surgical and animal handling procedures were in accordance with Canadian Council on Animal Care guidelines on the use of laboratory animals, and preapproved by the York University Animal Care Committee.…”
Section: Animals and Apparatusmentioning
confidence: 99%
See 2 more Smart Citations